If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(x + -5) = -1x Reorder the terms: -2(-5 + x) = -1x (-5 * -2 + x * -2) = -1x (10 + -2x) = -1x Solving 10 + -2x = -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 10 + -2x + x = -1x + x Combine like terms: -2x + x = -1x 10 + -1x = -1x + x Combine like terms: -1x + x = 0 10 + -1x = 0 Add '-10' to each side of the equation. 10 + -10 + -1x = 0 + -10 Combine like terms: 10 + -10 = 0 0 + -1x = 0 + -10 -1x = 0 + -10 Combine like terms: 0 + -10 = -10 -1x = -10 Divide each side by '-1'. x = 10 Simplifying x = 10
| -5+17x=48 | | 9-4x=-23 | | 6(3-x)=3x | | 20x^2=10+46x | | 8+7x=64 | | 4(3n+5)-2(2-4n)=6-2n | | 9x+6=16+4x | | 365=X^3 | | 4+5x-9= | | -5x+1=31 | | 5-7x=2x-5 | | -4(T-7)-(T+4)=9 | | 9x-7=27x+5 | | 39=2-3x | | x+1=5-2x | | 14(x+7)=-49(x-2) | | 23+28= | | 7(5z+1)=7 | | 7x-(3x-2)=14 | | 21r^2-133r-20=0 | | 9x-2=8x-5 | | 4x-2(4x)=54 | | 9(m-1)-9(2m+1)=-10(m+3)+7 | | 6(7+5x)=72 | | 4y+12=y-10 | | 3y-5x=13 | | 5x-4=x+20 | | x-9=-19 | | c^2+18c+32=0 | | 3y-8+y+28=6y+20-4y | | 16x-5=12x-25 | | 5x+40+x+80=180 |